2021
DOI: 10.3390/ijerph18073479
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Autoregulated Flywheel and Traditional Strength Training on Training Load Progression and Motor Skill Performance in Youth Athletes

Abstract: Background: The effects of flywheel resistance training (FRT) on youth are relatively unknown. The aim of this study was to compare the effects of autoregulated FRT with traditional strength training (TST) on jumping, running performance and resistance training load progression in youth athletes. Thirty youth athletes (11.8 ± 0.9 yr) were matched for peak height velocity (PHV) status and block-randomised into two groups: FRT (n = 15, PHV −0.8 ± 1.6) and TST (n = 15, PHV −0.8 ± 1.5). Twelve resistance training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Similarly, Raya-González et al [174] investigated the effects of a FIT lateral squat over 10 weeks in an under-16 age group of soccer players and found no improvements in sprint time over 10, 20 and 30 m. Nonetheless, the training intervention led to an increase in CMJ and COD performance. One important difference between these findings and those above [171,172,175] is that in the study by Westblad et al [173], progressions in intensity were achieved via autoregulation. Although the rationale behind autoregulation is to prevent excessive fatigue and therefore, incur greater adaptations [179], caution must be taken to ensure that appropriate supervision is in place, especially in children as young as those in this investigation (mean age 11.8 years) [173].…”
Section: Sprint and Cod Performancementioning
confidence: 65%
See 2 more Smart Citations
“…Similarly, Raya-González et al [174] investigated the effects of a FIT lateral squat over 10 weeks in an under-16 age group of soccer players and found no improvements in sprint time over 10, 20 and 30 m. Nonetheless, the training intervention led to an increase in CMJ and COD performance. One important difference between these findings and those above [171,172,175] is that in the study by Westblad et al [173], progressions in intensity were achieved via autoregulation. Although the rationale behind autoregulation is to prevent excessive fatigue and therefore, incur greater adaptations [179], caution must be taken to ensure that appropriate supervision is in place, especially in children as young as those in this investigation (mean age 11.8 years) [173].…”
Section: Sprint and Cod Performancementioning
confidence: 65%
“…The current review found FIT interventions to be the most frequently utilised ERT method in youth athletes (Table 4). These investigations incorporated several different measures to quantify physical before and after a FIT intervention, including sprint speed [171][172][173][174][175], COD performance [171,[174][175][176], NHE breakpoint angle [43], isometric strength [175], and numerous jumping tasks and metrics [43, 171-175, 177, 178]. The participants in these studies had a mean ± standard deviation age of 15.8 ± 2.0 years (range 11.8-18 years).…”
Section: Chronic Effects Of Fit On Physical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…En nuestra investigación se aplicó una progresión de la carga similar a la realizada por el estudio que también observó mejoras significativas del sprint (Marotoizquierdo et al, 2017). Es probable que la mayor ganancia porcentual en la velocidad de la carrera observada en nuestro estudio en comparación con otros reportes (Marotoizquierdo et al, 2017;Madruga-Parera et al, 2022;Westblad et al, 2021) se deba principalmente a las características de los participantes. Por ejemplo, en el estudio de Maroto-izquierdo et al, (2017) se intervino deportistas de elite, mientras que en nuestra investigación fueron personas no entrenadas.…”
Section: Discussionunclassified
“…20 Studies have shown that IFRT can be used in all stages of musculoskeletal injury rehabilitation to increase muscle strength and functional performance, from postsurgical to return to sport phases. [21][22][23] Tendinopathy represents a spectrum of tendon pathology, associated with changes to the structural tendon collagen matrix, presence of various inflammatory cells and clinical symptoms of pain and impaired performance, with potential for progression to a chronic degenerative condition. 24 Tendinopathy is common in athletes with high training demands and is associated with repetitive tendon microtrauma, with Achilles and patellar tendinopathy having the highest prevalence in athletes.…”
Section: Introductionmentioning
confidence: 99%